Homogenization and dimension reduction of the stokes problem with Navier-slip condition in thin perforated layers - Fabricius, John; Gahn, Markus (Multiscale modeling & simulation, 2023)
.This paper concerns the rigorous periodic homogenization for a nonlinear strongly coupled system, which models a suspension of magnetizable rigid particles in a nonconducting carrier viscous Newtonian fluid. The fluid drags the particles and thus alters the magnetic field. Vice versa, the magnetic field acts on the particles, which in turn affect the fluid via the no-slip boundary condition. As the size of the particles approaches zero, it is shown that the suspension’s behavior is governed by a generalized magnetohydrodynamic system, where the fluid is modeled by a stationary Navier-Stokes system, while the magnetic field is modeled by Maxwell equations. A corrector result from the theory of two-scale convergence allows us to obtain the limit of the product of several weakly convergent sequences, where the div-curl lemma, which is a typical tool in these types of problems, is not applicable.
Gesehen am 06.05.2024